2020
DOI: 10.1108/jmd-05-2019-0154
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of business leadership in the Eurasian context: empirical evidence from Kazakhstan

Abstract: PurposeBased on the tenets of the conservation of resources (COR) theory, this study investigated the influence of different leadership styles on organizational performance in the context of a Eurasian country (i.e. Kazakhstan). It further examined the moderating role of corporate culture in the leadership-organizational performance relationship.Design/methodology/approachUsing the quantitative survey method, the study collected data from 321 managerial employees working in local and multinational corporations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Both measurement and structural models are indispensable parts of SEM. They are tested by examining the reliabilities and validities to confirm the psychometric properties of scales and assess the path coefficients, significance levels, and p-values to assess the observed relationships ( Mahmood, Uddin, Ostrovskiy, & Orazalin, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Both measurement and structural models are indispensable parts of SEM. They are tested by examining the reliabilities and validities to confirm the psychometric properties of scales and assess the path coefficients, significance levels, and p-values to assess the observed relationships ( Mahmood, Uddin, Ostrovskiy, & Orazalin, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tang and Wei (2022) found that performance and creative self-efficacy are significantly impacted by ambidextrous leadership. Mahmood et al. (2020) stated that transactional leadership has a huge impact on staff performance.…”
Section: Resultsmentioning
confidence: 99%
“…An employee's performance improves when a good work-life balance culture is developed (Hermawati and Mas, 2017;Wolor et al, 2020). A good corporate culture that influences the workers' attitudes and behaviour, encourages workers to have a sense of belonging to their companies and results in the achievement of their goals and objectives (Mahmood et al, 2020) aids the leader in performing his good leadership.…”
Section: 2mentioning
confidence: 99%
“…Matzler et al (2020), in a study of 939 employees in a Germany-based technology company operating throughout 35 countries including Russia, Poland and Hungary, found that transformational leadership and top management communication are positively related to affective and normative commitment to change and that cultural distance moderated direct managers' transformational leadership and affective commitment relationship, reducing the influence of top management communication on normative commitment to change. Mahmood et al (2020) explored the influence of different leadership styles on organizational performance and the moderating role of corporate culture in a sample of 321 managers in both local and multinational corporations in Kazakhstan. They found that transformational, transactional and paternalistic leadership showed a stronger influence on performance than democratic/humaneoriented and authoritarian/autocratic leadership.…”
Section: Discussion Conclusion and Lessons Learnedmentioning
confidence: 99%